Agarwood essential oil revolution - Saiful Nizam, Tajuddin (Penerbit UMP, 2014)
Agarwood essential oil remains to be in high demand in the perfumery and aromatherapy industries globally. This is due to the healing properties in aromatherapy and the pleasant smell that perfumery releases. The high demand for the commodity can lead to some serious problems especially when there is a shortage in the natural resources.